Modelling game sports as complex systems – application of recurrence analysis to golf and soccer. Issue 4 (4th July 2017) - Stöckl, Michael; Plück, Denise; Lames, Martin
ABSTRACT: Analyses of game sports or of performances shown in them require appropriate models. Many game sports can be modelled as complex, dynamic systems. This study investigated how recurrence plots (RPs) – a method to analyse complex systems – and the analyses of RPs can be applied to the game sports golf and soccer. A golfer is treated as a complex system with many unknown components. The scalar variable Shots Saved can describe his/her behaviour. Phase space reconstruction is needed to unfold hidden facets of a golfer's behaviour. Results indicate that golfers' performances do not approach a stable state, but seem rather unpredictable. A soccer match can also be treated as a complex system. Some components – the players – and their respective behaviour represented by movement trajectories are known and can be used to describe the system's behaviour. We propose that no embedding is needed for the RP construction in this case. Results indicate that the more goal shots there are in a game, the more unstructured it is. Furthermore, if several golfers or soccer matches are investigated, we recommend using the same RP parameters to achieve comparable results.